Post-consumer wood – an additional reserve of raw materials for construction materials - Medvid, L.M. (Forestry, Forest, Paper and Woodworking Industry, 2021)
It is substantiated that post-consumer wood (PCW) is an alternative additional resource of raw materials under the condition of recycling and processing it into structural materials for use in the technological processes of woodworking, furniture and other wood products. The main problem of processing used wood is clarified – the lack of resource-saving and environmentally safe technologies with practical recommendations for the use of PCW in woodworking. The need to create a classification of used wood is substantiated, which will make it possible to record, identify, forecast the volume of formation and predict a potential reserve for the manufacture of new wood products. A detailed review and thorough analysis was made to determine the principles of classification of used wood. It is substantiated that the production of structural materials, in particular carpentry boards, can become a promising direction of material use of used wood, which is an urgent and understudied problem. It is substantiated that used wood can be processed into dimensionally suitable blanks, which are the basis for the manufacture of carpentry boards and carpentry boards of various designs. It has been established that the development of ways of use, classification of used wood, resource-saving and environmentally safe technology with practical recommendations for the use of PCW in woodworking will make it possible to significantly save primary raw materials. It has been found that the problem of finding a rational option for processing PCW into dimensionally suitable blanks for carpentry boards is urgent, and for its real solution, it is necessary to develop significant steps regarding the classification of PCW according to the degree of pollution, which is decisive for the production of quality products. The main strategic ways of using PCW, which formed the basis of the developed concept in the following areas: material and energy use, transformation and storage, are substantiated. A strategy for the use of PCW has been developed in compliance with the algorithm of the step-by-step material processing procedure, which is based on the systematization of PCW by categories, classification by pollution, the concept of utilization by processing into dimensionally suitable blanks and construction materials.